1984
DOI: 10.1126/science.223.4637.701
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Membranes in Anhydrobiotic Organisms: The Role of Trehalose

Abstract: Trehalose is a nonreducing disaccharide of glucose commonly found at high concentrations in anhydrobiotic organisms. In the presence of trehalose, dry dipalmitoyl phosphatidylcholine (DPPC) had a transition temperature similar to that of the fully hydrated lipid, whereas DPPC dried without trehalose had a transition temperature about 30 degrees Kelvin higher. Results obtained with infrared spectroscopy indicate that trehalose and DPPC interact by hydrogen bonding between the OH groups in the carbohydrate and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
933
0
26

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,415 publications
(1,000 citation statements)
references
References 20 publications
(33 reference statements)
32
933
0
26
Order By: Relevance
“…Both the maintenance of a proper intracellular Na ϩ balance and the accumulation of the compatible solute glycerol are key features of the osmoregulatory response in yeast cells (7). The disaccharide trehalose has been invoked as an agent in severe dehydration resistance by proposed membrane-stabilizing properties (13). Thus, regulation of genes involved in these processes is likely to be salinity controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Both the maintenance of a proper intracellular Na ϩ balance and the accumulation of the compatible solute glycerol are key features of the osmoregulatory response in yeast cells (7). The disaccharide trehalose has been invoked as an agent in severe dehydration resistance by proposed membrane-stabilizing properties (13). Thus, regulation of genes involved in these processes is likely to be salinity controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Among the naturally available disaccharides, trehalose appears to be the one of the most effective stabilizing agents. [1][2][3][4][5][6][7] Trehalose, which is also called mycose and mushroom sugar, 1 is a nonreducing homodisaccharide in which two D-glucopyranose units are linked together in an α − 1,1-glycosidic linkage.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, trehalose is accumulated in phases of nutrient starvation, desiccation, and after exposure to a mild heat shock (for reviews see Van Laere, 1989;Wiemken, 1990;Crowe et al, 1992). It has been suggested, therefore, that trehalose plays a role as a stabiliser of cellular structures under stress conditions (Keller et al, 1982;Crowe et al, 1984). In accordance with this suggestion, in vitro studies have revealed the exceptional capability of trehalose in protecting biological membranes and enzymes from freezing-or drying-induced dehydration (for a review see Crowe et al, 1992) and heat stress (Hottiger et al, 1994).…”
Section: Introductionmentioning
confidence: 99%